The Birth of the Three Great Islamic Kingdoms in the Middle Ages (1250-1800 AD) - Fauzan, Elda Harits; Setiawan, Agus Mahfudin (Universitas Islam Negeri Raden Intan Lampung, 2022)
Islam had a very advanced civilization, namely during the Abbasid dynasty. More precisely when Caliph Harun Al Rashid and his son Al Ma'mun led, around the 8th century AD to the 13th century AD. Harun Al Rashid and his son Al Ma'mun have big aspirations, namely to build an Islamic civilization that upholds science. But unfortunately this golden age of Islam must end. There are several factors that caused the end of this golden age of Islam. However, the most significant was the result of an attack from the Mongols that destroyed Baghdad along with the most complete library and center of knowledge at that time, Bayt Al Hikmah. This attack from the Mongols also caused the political power of Islam to be divided. Where the Islamic territory is no longer in one big unit, which is led by one leader who becomes the caliphate as the center of government. Islamic political conditions began to develop again and began to show progress after the emergence of the three great Islamic empires in the Middle Ages. The three great kingdoms, the Ottoman Empire in Turkey, the Mughal Empire in India, and the Shafavid Empire in Persia.Keywords: Conquest, Golden, Civilization